The Double-Edged Sword of RP: the Contrasting Roles of a Pronunciation Model in both Native and Non-native Environments - Ježek, Miroslav (Research in Language, 2012)
Received Pronunciation (RP) is often studied as the pronunciation model in Great Britain and non-English-speaking countries separately. What my paper focuses on is the duality with which RP is essentially endowed: the role(s) in which it has to satisfy the needs of both native and non-native speakers of English. Whilst the claim that RP has changed recently goes unchallenged, the issue of reflecting these changes in the preferred transcription models is hotly debated. Upton’s model of RP is one that does include several new symbols, motivated by an attempt to ‘ensure that the description of a late twentieth century version the accent […] looks forward to the new millennium rather than back at increasingly outmoded forms’ (2001:352). I discuss the feasibility of adopting Upton’s model of RP as the pronunciation model in non-English speaking countries, where it is desirable to resolve the paradox that ‘most of our teaching is aimed at young people, but the model we provide is that of middle-aged or old speakers’ (Roach 2005: 394). The observations I make are largely based on my MA research, which is now being modified for the purposes of my Ph.D. I asked undergraduate students of English in England and the Czech Republic to evaluate seven voices ranging from the clearly regional to the unquestionably RP. The objective was to discover which sounds are considered to fall within the scope of RP by students in both countries, which approach avoids treating RP as though it were to include only the sounds ‘allowed by a preconceived model’ (Upton 2000: 78). Further, the respondents were asked to comment on the most salient features in the recordings: what they opted to comment on reveals a marked difference in the role of RP as a model accent in the given countries. Societies which lack a prestigious non-regional accent are often oblivious to the social connotations RP carries. Whilst it seems technically impossible to replace the model accent in all teaching materials all over the world, creating awareness of the fact that a rather outmoded model of RP found in many textbooks may not always be the best option is a necessary step towards ensuring that non-English speaking students are not only understood but that their speech will attract no adverse judgements.